Does increased photorespiration protect the leaves of common reed living in fragmented patches from excess light? - Dulai, Sándor (Acta Biologica Szegediensis, 2002)
The effects of non-photorespiratory conditions on some photosynthetic parameters were studied in the leaves of common reed from fragmented patches and closed stands at 1500 umol m2 AL intensity. At the steady-state photosynthesis level there was no significant difference in the effective quantum yield of PS II (DFIFm') between untreated leaves from closed stands and fragmented patches. The application of phosphinothricin (PPT) and air containing 2% 02 resulted in a substantial decrease in DFIFm', which was more significant in leaves from fragmented patches. Both PPT and low oxygen tension produced a similar effect on DFIFm'. In addition the photorespiration (R) was twice as high in leaves from fragmented patches than in closed stands and in parallel with this a linear regression ratio was found between RP and in vitro GS activity. The results suggest that the leaves of fragmented patches and closed stands might have divergent defensive strategies against excess light.